KONSEP PEMBAHARUAN HUKUM AGRARIA SESUAI AMANAT UUD 1945 - Nirwan Yunus (Universitas Negeri Gorontalo, 2009)
The demand of land reform implementation increases recently. The imbalance of land athority and the demand of land acceas as well qs other productive resources of the poor are getting stronger in most of the third world country. Builds the law is not work which is easy and or simple like the one is imagined, because a good law and regulation must up to standard of justice, rule of law and utility in balance. and so in effort for agrarian law forming process which more accommodating all importances of all sides. Must be realized and confessed act No 5 the year 1960 still leaving various problems which must be broken.